Evaluasi Pendapatan dan Strategi Pemasaran dalam Usaha Pertanian Cabai Merah (Capsicum annum L.) Desa Puncu Kabupaten Kediri - Putro, Wahyu Rianto; Sidhi, Eko Yuliarsha; Sutiknjo, Tutut Dwi; Pamujiati, Agustia Dwi; Djoko Rahardjo (Jurnal Ilmiah Pertanian Nasional, 2024)
The development of the agricultural sector has the main objective of increasing food production and nutrition and improving the standard of living and welfare of the community. One of the potential contributors to the income of the farmers studied is the red chili plant. This research was conducted in Puncu Village, Kediri Regency, as a red chili production center. The research used a census method with 15 red chili farmer respondents. Data collection was carried out through interviews and questionnaires with farmers and traders. Data analysis was carried out qualitatively and quantitatively. The research results show that red chili farming in Puncu Village, Kediri, produces an average of 8,823 kg/ha with a total production cost of IDR34,594,639 per hectare. Farmers' income reaches IDR218,218,667, so the profit per hectare reaches IDR183,624,028 with an R/C ratio of 6.43, indicating significant profits. Red chili marketing was carried out through two channels where the first channel (farmers to retailers to consumers) was classified as efficient, with an efficiency level of 1.07%. Meanwhile, the second channel (farmer to collector to retailer to consumer) could be more efficient, with an efficiency level of 3.13%. Analysis of costs, profits, and marketing efficiency provides a deeper understanding of the economic dynamics in the red chili sector in Puncu Village, Kediri.   Pembangunan sektor pertanian memiliki tujuan utama untuk meningkatkan produksi pangan dan gizi, serta meningkatkan taraf hidup dan kesejahteraan masyarakat. Salah satu potensi penyumbang pendapatan petani yang diteliti adalah tanaman cabai merah. Penelitian ini dilakukan di Desa Puncu, Kabupaten Kediri, sebagai sentra produksi cabai merah. Penelitian menggunakan metode sensus dengan 15 responden petani cabai merah. Pengumpulan data dilakukan melalui wawancara dan kuesioner kepada petani dan pedagang. Analisis data dilakukan secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa usahatani cabai merah di Desa Puncu, Kediri, rata-rata menghasilkan 8.823 kg/ha dengan total biaya produksi Rp34.594.639 per hektar. Penerimaan petani mencapai Rp218.218.667, sehingga keuntungan per hektar mencapai Rp183.624.028 dengan R/C ratio 6,43, menandakan keuntungan yang signifikan. Pemasaran cabai merah dilakukan melalui dua saluran, dimana saluran pertama (petani ke pedagang pengecer ke konsumen) tergolong efisien dengan tingkat efisiensi 1,07%. Sementara itu, saluran kedua (petani ke pedagang pengumpul ke pedagang pengecer ke konsumen) tidak efisien dengan tingkat efisiensi 3,13%. Analisis biaya, keuntungan, dan efisiensi pemasaran memberikan pemahaman lebih mendalam tentang dinamika ekonomi di sektor cabai merah di Desa Puncu, Kediri.